Predicting role of mindfulness and procrastination on psychological well-being among university students in Malaysia - Anusha Raj Jayaraja; Tan, Soon Aun; Puspu Nanthinni Ramasamy (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study aimed to investigate the predicting role of mindfulness and procrastination on psychological well-being among university students. A total of 449 university students from both public and private universities were recruited using convenience sampling method. This quantitative correlational research used Mindfulness Attention Awareness Scale (MAAS) to measure mindfulness whereas General Procrastination Scalewas used to measure procrastination. Psychological well-being, the dependent variable, was tested using the Ryff’s Scale of Psychological Well-being. The study showed a significant relationship between mindfulness, procrastination and psychological well-being among university students. Besides, the results also revealed that procrastination was the strongest predict or of students’ psychological well-being. The findings of this study may be beneficial to practitioners, universities, parents and individuals in order to further comprehend the current status of psychological well-being among university students. Programs and implementations should endorse the circumstance that certain form of procrastination indeed enhances performance and well-being of students.